2020
DOI: 10.4081/pr.2020.8703
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Parents’ Self-efficacy and Quality of Life of Children with Cancer Aged 8-12 Years

Abstract: This study aims to determine the correlation between parents’ self-efficacy and the quality of life of children with cancer aged 8- 12 years. Quantitative research using a crosssectional design was carried out on 39 parents and 39 children with cancer. The participants were selected using a consecutive sampling method. The measurement instruments used were the Self-Efficacy for Parenting Task Index (SEPTI), the Pediatric Quality of Life InventoryTM (PedsQLTM) 4.0 Generic Core Scale, and the PedsQLTM 3.0 Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
1
7
1
Order By: Relevance
“…When exploring the role of self‐efficacy, previous research has supported the beneficial role of self‐efficacy for psychosocial functioning in parents of children with cancer 17 . However, this was not supported by the present data, both in mothers and fathers.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…When exploring the role of self‐efficacy, previous research has supported the beneficial role of self‐efficacy for psychosocial functioning in parents of children with cancer 17 . However, this was not supported by the present data, both in mothers and fathers.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study aimed to evaluate whether PS was associated with ED through perceived control and self‐efficacy in couples of parents. In line with theory, we hypothesized that when placed in the same model, both perceived control and self‐efficacy would emerge as intermediary variables in the relationship between PS and ED 13,17 …”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…These are things that should be considered in children with cancer because of their special needs. This nding is in line with the results of some studies [15][16][17][18]. Also, studies aimed at investigating the effect of family-centered education on increasing parental awareness and self-e cacy in weight control and physical activity and caring for a child with asthma and epilepsy, showed that education can increase self-e cacy and improve home care effectively [19][20][21][22].…”
Section: Discussionsupporting
confidence: 85%